SHIELD TUNNELLING 3D NUMERICAL SIMULATION ON THREE CASE STUDIES (Malaysian Journal of Civil Engineering, 2018)
In congested urban areas, shallow tunnel constructions are sometimes necessary due to lack of space. Therefore, a careful assessment of their effects on existing constructions is vitally required. In the application of shield tunnel boring machines (TBM), different operations conducted may induce a three-dimensional problem of soil/structure interaction. They are complicated to be represented in a complete numerical simulation that allows evaluation of induced ground movements, in particular surface settlement assessment. A three-dimensional simulation procedure, using finite differences code Flac-3D, taking into account an explicit manner of the main origins of movements in soil mass, is hereby presented in this paper. It is applied to three different tunnel construction sites, with different types of face support and soils (i.e. nature and mechanical characteristics). Results have been compared to those obtained from in-situ measurements during construction. It shows that the proposed 3D simulation procedure is highly relevant, particularly in the adopted representation for different operations performed by tunnel boring machine (excavation, confining pressure, advancement, installation of lining, grouting of annular void, etc.).